2014
DOI: 10.1152/ajpheart.00655.2013
|View full text |Cite
|
Sign up to set email alerts
|

Variation of mechanical properties and quantitative proteomics of VSMC along the arterial tree

Abstract: Vascular smooth muscle cells (VSMCs) are thought to assume a quiescent and homogeneous mechanical behavior after arterial tree development phase. However, VSMCs are known to be molecularly heterogeneous in other aspects and their mechanics may play a role in pathological situations. Our aim was to evaluate VSMCs from different arterial beds in terms of mechanics and proteomics, as well as investigate factors that may influence this phenotype. VSMCs obtained from seven arteries were studied using optical magnet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 46 publications
0
47
0
6
Order By: Relevance
“…For example, Guo and Kassab (2004) observed a lower stretch ratio and Cauchy stress in the porcine thoracic aorta, and Roach and Song (1994) observed that the abdominal aorta tears more easily while needing higher pressure for propagation of the defect when liquid is injected into the tunica media. Dinardo et al (2014) observed higher stiffness in the abdominal aorta due to reduced elastin content. In addition to the mechanical function of elastin in the aortic wall, this protein might be important in the progression of inflammatory changes because Lannoy et al (2014) observed elastin, together with fibrillin, acts as an autocrine factor that regulates the activity and availability of TGFs within the tissue.…”
Section: The Thoracic Aorta Has a Different Composition Than The Abdomentioning
confidence: 87%
See 1 more Smart Citation
“…For example, Guo and Kassab (2004) observed a lower stretch ratio and Cauchy stress in the porcine thoracic aorta, and Roach and Song (1994) observed that the abdominal aorta tears more easily while needing higher pressure for propagation of the defect when liquid is injected into the tunica media. Dinardo et al (2014) observed higher stiffness in the abdominal aorta due to reduced elastin content. In addition to the mechanical function of elastin in the aortic wall, this protein might be important in the progression of inflammatory changes because Lannoy et al (2014) observed elastin, together with fibrillin, acts as an autocrine factor that regulates the activity and availability of TGFs within the tissue.…”
Section: The Thoracic Aorta Has a Different Composition Than The Abdomentioning
confidence: 87%
“…Guo and Kassab, 2004;Sokolis et al, 2008;Dinardo et al, 2014). Most authors directly attributed the differences in the mechanical behavior of the aortic wall to different elastin content in the tunica media.…”
Section: The Thoracic Aorta Has a Different Composition Than The Abdomentioning
confidence: 99%
“…It is also still not well understood why 60% of TAAs occur in the AA. Susceptibility of different vascular regions to TAAs has been attributed to locational differences in blood flow (10), endothelial permeability (42), ECM content and SMC mechanical properties (20), SMC gene expression (88), SMC embryonic origin (53), or SMC response to signaling molecules (60,80). Fibulin-4 knockout (Fbln4 Ϫ/Ϫ ) mice display opposite vascular phenotypes depending on the thoracic location, with aneurysms developing in the AA and narrowing occurring in the descending aorta (DA) (34,55), and represent a unique model to study differences in TAA susceptibility of specific locations.…”
mentioning
confidence: 99%
“…It is well known that aging affects arterial structure and function (31,40). Arterial wall stiffness increases with aging due to increases in collagen content and cross-linking, a high collagen-to-elastin ratio, increased medial wall thickness, and vascular calcification (9,10,12,30,31). In addition, it has been reported that sex affects the mechanical properties, biochemical contents, and wall structure of arteries (41).…”
Section: Discussionmentioning
confidence: 99%